Microscale Heat Transfer - Fundamentals and Applications Proceedings of the NATO Advanced Study Institute on Microscale Heat Transfer - Fundamentals and Applications in Biological and Microelectromechanical Systems, Cesme-Izmir, Turkey, 18-30 July, 2004 - Kakaç, S.; Kakaç, S.; Vasiliev, L.L.; Vasiliev, L.L.; Bayazitoglu, Y.; Bayazitoglu, Y.; Yener, Y.; Yener, Y. (Nato Science Series II:, Mathematics, Physics and Chemistry,, 2005)
This volume contains an archival record of the NATO Advanced Institute on Microscale Heat Transfer – Fundamental and Applications in Biological and Microelectromechanical Systems held in Çesme – Izmir, Turkey, July 18–30, 2004. The ASIs are intended to be high-level teaching activity in scientific and technical areas of current concern. In this volume, the reader may find interesting chapters and various Microscale Heat Transfer Fundamental and Applications. The growing use of electronics, in both military and civilian applications has led to the widespread recognition for need of thermal packaging and management. The use of higher densities and frequencies in microelectronic circuits for computers are increasing day by day. They require effective cooling due to heat generated that is to be dissipated from a relatively low surface area. Hence, the development of efficient cooling techniques for integrated circuit chips is one of the important contemporary applications of Microscale Heat Transfer which has received much attention for cooling of high power electronics and applications in biomechanical and aerospace industries. Microelectromechanical systems are subject of increasing active research in a widening field of discipline. These topics and others are the main themeof this Institute.